Performance analysis of Fog and Cloud Nodes for Cognitive Internet of Things - Eusufzai, Fariha; Haq, Tahmidul; Chowdhury, Sumit; Sahren, Shohani (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2020.